KINETIC APPROACH OF THE LOWER LIMB TRAUMA IN MOUNTAIN RUNNING - Mihai Constantinescu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Running has been and is one of the favorite activities of most people's, in that it produces a variety of positive effects on the human body. A runner wishes at one point, to leave the classical trails and diversify with mountain running.